2020
DOI: 10.22545/2020/00139
|View full text |Cite
|
Sign up to set email alerts
|

Being in the Hidden Third: Insights into Transdisciplinary Ontology

Abstract: This paper reflects two transdisciplinary (TD) scholars’ attempts to glean deeper insights into Nicolescu’s transdisciplinary ontology (i.e., multiple Levels of Reality and the Hidden Third). Respecting that Nicolescu’s Hidden Third represents the convergence of quantum physics, philosophy, and inner experiences, one TD scholar explored ‘What is it like to be in the Hidden Third?’ by expanding on Nicolescu’s constructs of cyber-space-time and transhumanism, which are grounded in quantum physics. The other TD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results of talent success factors according to quantitative and qualitative data indicated that the most important factor for ODT is TOT. This finding corresponds to aiding firms in demonstrating their capability to adapt to new circumstances and solve complex issues [6,7,52,90,92,112]. Transdisciplinary is essential with the evolution of inter-disciplinary and multidisciplinary approaches to operating a firm in a VUCA environment with a unique strategy [4,55,[111][112][113][114].…”
Section: -Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results of talent success factors according to quantitative and qualitative data indicated that the most important factor for ODT is TOT. This finding corresponds to aiding firms in demonstrating their capability to adapt to new circumstances and solve complex issues [6,7,52,90,92,112]. Transdisciplinary is essential with the evolution of inter-disciplinary and multidisciplinary approaches to operating a firm in a VUCA environment with a unique strategy [4,55,[111][112][113][114].…”
Section: -Discussionmentioning
confidence: 93%
“…While agility and an eagerness to learn new things are essential in a data-driven culture, establishing digital capital in organizational digital transformation are critical [51]. While transdisciplinary [6,7,52] highlights continuous learning in managing complexity, problem-solving, and a greater degree of abstraction for epistemology, not just own professions, with interdisciplinary pertinence [4], there is inherent uncertainty about its compatibility with an exponential mind-set or its ability to reconcile borderless bounds.…”
Section: -1-organizational Digital Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption instead is that disciplinary knowledge is simply not enough. Other ways of living with, being in and seeing the world are needed (McGregor & Gibbs, 2020;Nicolescu, 2014).…”
Section: Introductionmentioning
confidence: 99%